Urban youths go 3000 miles: engaging and supporting young residents to conduct neighborhood asset mapping. - Santilli, Alycia; Carroll-Scott, Amy; Wong, Fiona; Ickovics, Jeannette (American journal of public health, 2011)
In 2009, CARE (Community Alliance for Research and Engagement at Yale University) launched a multisectoral chronic disease prevention initiative that conducts baseline data collection, interventions, and follow-up data collection to measure change. Data collection includes asset mapping to assess environmental determinants of chronic disease risk factors in neighborhoods and around schools. CARE hired 7 local high school students to conduct asset mapping; they walked more than 3000 miles and collected 492 data points. Employing youths as community health workers to collect data greatly enriched the community research process and offered many advantages. We were able to efficiently and effectively conduct scientifically rigorous mapping while gaining entry into some of New Haven's most research-wary and skeptical neighborhoods.
Keywords: Adolescent; Chronic Disease; Community Health Workers; Community-Institutional Relations; Data Collection; Humans; Needs Assessment; Residence Characteristics; Students; Urban Population; Young Adult